Burden of nosocomial infections in intensive care units: Cost of antibiotics, the extra length of stay and mortality rate - Masoome Zolfaghari; Arash Seifi; Ebrahim Jaafaripooyan; Zahra Jahangard-Rafsanjani; Shirin Afhami; Mostafa Mohammadi; Mohammad Masoud Emami Meybodi; Mohammadreza Salehi; Esmaeil Mohammadnejad (Babol University of Medical Sciences, 2024)
Background: Healthcare-associated infections (HAIs) in intensive care unit (ICU) patients significantly complicate the normal hospitalization process and affect patients' condition, length of hospitalization, mortality, and treatment cost. In this study, we aimed to determine the prevalence and economic burden of HAIs. Methods: The study involved all patients with a confirmed HAIs (based on CDC/NHSN case-definitions); in the general ICU of a tertiary university hospital in Tehran, from April 2020 to March 2021. The patients' information, including length of hospitalization, outcome, type and cost of prescribed antibiotics, were recorded. Results: During the study period, 119 HAIs were found in 1395 (43% F / 57% M) patients. The prevalence of nosocomial infections was 8.53%. The mean duration of hospitalization in all ICU patients was 4.7 ± 3.1 days, and 31.85 ± 18.96 days in patients with HAIs. The most common organisms involved in HAIs are Acinetobacter baumannii (54.6%), Klebsiella pneumoniae (30.3%), E. coli (15.1%), and Enterococcus spp. (12%). Incidence density of ventilator-associated pneumonia (VAP), central line-associated bloodstream infection (CLA-BSI), and catheter-associated urinary tract infection (CA-UTI) per 1000 device-days were 36.08, 17.57, and 8.86, respectively. The total cost of antibiotics for HAIs was € 105,407. Among these, the highest consumption costs were for carbapenems, followed by colistin and caspofungin. Conclusion: This study showed the high burden of nosocomial infections in ICUs. Strategies for more strict infection prevention and control are necessary to reduce this burden.